Role of Financial Statement in Investment Decision Making Process - Bhujel, Suraj (Journal of Balkumari College, 2020)
It is believed that financial statements are the key documents for any organizations for the investment decision making. Investment decision making depends upon the quality information obtained by the various sources and it is concluded in this research which is based on the findings that financial statement plays a vital role in investment decision making and recommends that no investment decision should be taken without the consideration of a company’s financial statements.